2017
DOI: 10.1086/690195
|View full text |Cite
|
Sign up to set email alerts
|

Timing Control without Docket Control

Abstract: The Brazilian Supreme Court has developed an informal mechanism of timing control: each justice has the power (pedido de vista) to request more time to study the files of a given case. In this article, we use a database of over 1.5 million cases to calculate vista request duration and compare vista behavior to other activities in which caseload and the justice’s efficiency play a role. Our results show that vistas can function as an individual power, unconstrained by the Court’s internal rules of procedure, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 9 publications
0
10
0
6
Order By: Relevance
“…Typically, a “vista” request can delay a judgment for many months and, in some cases, years. As Arguelhes and Hartman () argue, this is a de facto veto power every judge holds over cases. By this mechanism, “justices can simply remove ‘wrong’ cases from the agenda or prevent the ‘right’ cases from being judged at the ‘wrong’ time” (Arguelhes & Hartman :108).…”
Section: Institutional Settingmentioning
confidence: 99%
“…Typically, a “vista” request can delay a judgment for many months and, in some cases, years. As Arguelhes and Hartman () argue, this is a de facto veto power every judge holds over cases. By this mechanism, “justices can simply remove ‘wrong’ cases from the agenda or prevent the ‘right’ cases from being judged at the ‘wrong’ time” (Arguelhes & Hartman :108).…”
Section: Institutional Settingmentioning
confidence: 99%
“…However, there is no rule that obliges this justice to withdraw the lawsuit, so he or she can keep it stopped as long as he or she wishes. Arguelhes and Hartmann (2017) showed that this rule works as an extra-o cial docket control mechanism. According to the authors, justices will also employ pedidos de vista to prevent cases from being judged.…”
Section: The Agenda Powers Of Every Justicementioning
confidence: 99%
“…Common strategies used by justices, among others, are: a) the employment of an institutional mechanism called "pedido de vista, " which allows any justice to delay a judgment in order to give the case greater deliberation; (Arguelhes & Hartmann, 2017;Arguelhes & Ribeiro, 2016); b) the role of the rapporteur to stop a case or make decisions by him/herself without consulting other justices, (Arguelhes & Ribeiro, 2016, 2018a, 2018bHartmann & da Silva Ferreira, 2016) and; c) the role of the head of the Supreme Court to determine which lawsuits will be judged. I argue that the institutions emphasized in this new literature might have implications on traditional phenomena studied in judicial politics, such as judicial independence.…”
Section: Introductionmentioning
confidence: 99%
“…The past decade has witnessed dramatic growth in the empirical analysis of apex courts worldwide, from Argentina (Muro et al ) and Brazil (Arguelhes & Hartmann ) up to Canada (Alarie & Green ) and from Taiwan (Chen et al ) across the globe to Israel (Weinshall‐Margel ) and most of Europe (Hanretty forthcoming). This is welcome news because studies of judicial behavior add to the store of knowledge on law and legal institutions, provide guidance to policymakers, educate the public about their courts, help lawyers develop strategies, and even prompt judges to rethink their choices (Posner ; Epstein et al ; Wistrich et al ).…”
Section: Introductionmentioning
confidence: 99%